Maternal Death Self-Risk Perception as a Predictor of Women’s Delivery Site Preferences in Ile-Ife, Nigeria - Esan, Oluwaseun; Grace Okonta, Uchechi; Samuel Oladapo, Oluwaseun; Phillip Gbolade, Adetomiwa; Adebayo Oyewole, Tesleem (Journal of Maternal and Child Health, 2024)
Background: Increased uptake of health facility delivery could improve the worsening maternal mortality in low and middle-income countries. Several factors that determine women’s preferred delivery site had been reported in the literature, but none had explored women’s self-perception of maternal death as a predictor of their delivery site, hence this study. Subjects and Method: A cross-sectional study of 183 women recruited serially at the immunization clinic of two primary health facilities in Ile-Ife, Nigeria. Data was obtained using an interviewer-administered questionnaire. Their maternal death self-risk perception score by type of delivery site was determined with a minimum and maximum obtainable score of 7 and 35. Descriptive and inferential statistical analysis was done including a simple and multiple binary logistic regression. Results: The mean age of the respondents (Mean= 29; SD= 5.26). About 130 (71.0%) of the women delivered at a health facility. The majority of the women (91.8%) were aware of maternal death, while 32 (17.5%) feared death in their last pregnancy, with a mean maternal death self-risk perception score ((Mean= 24.96; SD= 2.69) (95% CI= 24.55 to 25.33)). The higher the maternal death self-risk perception score, the greater the odds of a facility-based delivery (AOR=1.40, 95% CI=1.20 to 1.64, p<0.001). However, alongside other confounding variables, only a facility-based ANC registration (AOR= 607.52, 95% CI= 1.39 to 2.66*105, p=0.039) and women’s personal reasons (AOR=0.02; 95%CI= 0.01 to 0.51; p=0.018) significantly influenced delivering at a health facility and non-health facility respectively. Conclusion: The place of ANC registration and personal reasons such as the women’s influential decision-makers better predicted their eventual delivery site. Nonetheless, the development and standardization of maternal death self-risk perception criteria for women is encouraged.